Synthesis, characterization, swelling-deswelling properties of Novel nanoparticle-hydrogel containing core chitosan and their cyclohexanone-crosslinked counterparts. Issue 9 (13th June 2019) - Bary, E. M. Abdel; Harmal, Ammar N.; Gouda, Moustafa A.
ABSTRACT: Novel Chitosan-cyclohexanone Mannich based hydrogel nanoparticles (CCMb 1-4) were prepare via the reaction of chitosan with different concentration of 2, 6-bis (piperidin-1-ylmethyl) cyclohexanone. 2HCl (1%, 5%, 10% and 15% wt/wt) at 70–80°C for 7 h. These hydrogels were subjected to equilibrium swelling studies at room temperature in solutions of pH 2, 4, 6 and 8. The (CCMb 1-4) showed maximum percent swellability at pH = 2.0. Furthermore, the swelling of the (CCMb 1-4) followed Fickian diffusion. This preliminary investigation of chitosan-based interpolymeric hydrogels showed that they may be exploited to expand the utilization of these systems in drug delivery applications. Graphical Abstract: